Sustainable development goals and the role of zakat - Muhammad Ahmad, Shamsuddeen; Mahadi, Nur Farhah (Lembaga Zakat Negeri Kedah, 2019)
The paper examines the potential of the institution of Zakāt to address the development challenges, especially in the Muslim world. We discuss the religious dimension of Zakāt. We also explore the economic potential and effects of Zakāt by reviewing theoretical and empirical studies. Finally, the study provide an analysis which suggests that Zakāt can play a significant role in meeting sustainable development goals related to poverty, hunger, global health and well-being, quality education, decent work and economic growth and income inequality